Evaluation of an insect meal of the Black Soldier Fly (Hermetia illucens) as soybean substitute: Intestinal morphometry, enzymatic and microbial activity in laying hens. (April 2018) - Cutrignelli, Monica Isabella; Messina, Maria; Tulli, Francesca; Randazzo, Basilio; Olivotto, Ike; Gasco, Laura; Loponte, Rosa; Bovera, Fulvia
Abstract: This research investigated the ileum morphometry and enzymatic activity, the caecal volatile fatty acid production and the apparent nutrient digestibility in laying hens fed a Hermetia illucens larvae meal (HILM) as a complete replacement of diet soybean meal (SBM). The hens fed HILM exhibited a lower live weight ( P < 0.05) and a higher incidence of the full digestive tract ( P < 0.05) than the SBM group. In the duodenum, the maltase exhibited a higher ( P < 0.05) activity in the HILM group while the intestinal alkaline phosphatase (IAP) had a higher (P < 0.05) activity in the SBM group. In the ileum, the maltase and saccarase had a higher activity in the HILM hens ( P ≤ 0.01) while the IAP and ɤ glutamil transferase had a higher activity in the SBM group ( P < 0.05 and P < 0.01, respectively). The HILM group showed a higher (P < 0.05) villi height in the duodenum, while the opposite happened in the jejunum and the ileum. Only in the ileum the crypt depth resulted higher ( P < 0.05) in the HIML group than in the SBM. The higher production of acetate (P < 0.05) and butyrate ( P < 0.01) affected the total production of volatile fatty acids of the HILM group. The coefficient of apparent digestibility of dry and organic matter as well as of crude protein was higher ( P < 0.05) in SBM group. The total replacement of SBM with HILM in laying hens diet from 24 to 45 weeks of age resulted in a higher caecal production of butyric acid while the enzymatic activities of brush border membrane were partially reduced. Highlights: The effect of Hermetia illucens on intestinal morphometry and activity of laying hens was studied. The insect meal decreased digestibility and modified enzymatic activity in the small intestine. Dietary inclusion of insect meal enhanced the production of butyric acid in the caeca.